Online Research and Media Skills: An instructional model to support students as they search and shift online informational text - O'Byrne, W. Ian; McVerry, J. Gregory (Using Technology to Enhance Reading: Innovative Approaches to Literacy Instruction, 2015)
Enhance students' reading abilities with technology. Discover how technological resources can improve the effectiveness and breadth of reading instruction to build student knowledge. Read real-world accounts from literacy experts, and learn how their methods can be adapted for your classroom. Explore how to foster improvement in student learning using a variety of tools, including interactive whiteboards, tablets, and social media applications. Benefits:Gain insight into ways to incorporate technology into reading instruction.Obtain guidance on choosing progress-monitoring tools to best address your students' needs. Discover strategies to engage students in vocabulary instruction, and help students interpret informational texts. Learn how to use various tools to spark group discussions about literature. Determine how to continually assess students' connections with the assigned reading material. Contents: Part I: Reading Foundations Chapter 1: Foundational Reading Competencies Supported With Technology: Phonemic Awareness and Word Recognition Chapter 2: Rethinking Foundational Reading Skills: Making Room for the Complexities of Digital Texts Chapter 3: Using Tablets to Teach Foundational Skills: Matching Apps to Student NeedsPart II: Reading Fluency Chapter 4: Podcasts: Adding Power and New Possibilities to the Readers Theater Experience Chapter 5: Student-Produced Movies as Authentic Reading Fluency Instruction Chapter 6: Audio-Assisted Reading Builds Reading FluencyPart III: Reading Vocabulary Chapter 7: Post-Reading Vocabulary Development Through VSSPlus Chapter 8: Bringing Words to Life Through Student-Created Vocabulary Videos Chapter 9: Self-Regulated Vocabulary Learning on the InternetPart IV: Comprehension of Informational Texts Chapter 10: Using the Multimodal Explanatory Composition Strategy to Respond to Informational Texts Chapter 11: Annotation Apps: Supporting Middle School Students' Interpretation of Science Texts Chapter 12: Online Research and Media Skills: An Instructional Model for Online Informational TextsPart V: Comprehension of Literary Texts Chapter 13: Digging Deeper With Reader Response: Using Digital Tools to Support Comprehension of Literary Texts in Online Learning Environments Chapter 14: Coding and Connecting Complex Literature Chapter 15: Linking Through Literature: Exploring Complex Texts Through Hypertext Literary AnalysisPart VI: Reading Across Disciplines Chapter 16: Classroom Blogging to Develop Disciplinary Literacy Chapter 17: Using eReaders to Enhance Literacy Instruction in the Content Areas Chapter 18: Supporting Inquiry With Digital Texts in School DisciplinesPart VII: Motivation for Reading Chapter 19: "I Wanted to Film, So I Read the Book": Filmmaking in the English Classroom Chapter 20: eBooks and eReaders: Removing Obstacles, Improving Motivation Chapter 21: Using Literacy iPad Apps for Reading MotivationPart VIII: Reading Assessment Chapter 22: Literacy Assessments in the Digital Age Chapter 23: Developing and Assessing Fluency Through Web 2.0 Digital Tools Chapter 24: Using Blogs as Formative Assessment of Reading Comprehension
Keywords: dept.cur

Implicit Attitudes of International and American Adult Students toward Black and White Teachers - Na, Eunkyung; Tan, Tony X.; Marn, Travis; Ramirez, Rica (Commission for International Adult Education, 2015)
The purpose of this study was to examine hidden prejudice in two groups of adult students, international and American, against black compared to white teachers. Social desirability in the minds of participants may affect the result of a study involving racial bias (Mullins, 1982). For this reason, the researchers created a computer protocol using the standard Implicit Association Test (IAT) to measure the implicit attitudes of participants. The IAT relies on the idea of automatic information process within the mind that is not impacted by social desirability. A clear concern in education is that the racial bias toward minority students will let those implicit biases affect the way they teach those students, creating a self-fulfilling prophesy of poor student performance. But the implicit bias can work both ways and can impact a teacher's effectiveness. Traditional racial prejudice theories usually looked at white's attitudes toward blacks and other groups. This study had a significant directional shift by focusing on the international students' racial attitudes toward black and white teachers. The implicit racial attitudes of international students were also compared to those of American students. The result and evaluation of this study may be a valuable tool to improve student services and teacher professional development in higher education. Suggestions for future research are also provided.[For full proceedings, see ED570489.]
Keywords: Adult Students; African American Teachers; Attitude Measures; College Students; Comparative Analysis; Foreign Students; Gender Differences; Racial Attitudes; Racial Bias; Social Desirability; Statistical Analysis; Student Attitudes; Surveys; Whites; dept.cur

Biracial Place Walkers on Campus: A Trioethnography of Culture, Climate, and Currere - Agosto, Vonzell; Marn, Travis; Ramirez, Rica (International Review of Qualitative Research, 2015)
Send this e-mail to Rica and Travis: Rica and Travis, I wish you could have been at the duoethnography panel. The first presentation had some uneasy conversations. The second, Dr. Colomer's presentation, was cool: A performance with guest actors had some sad moments with death, health issues, and attrition. The next presentation was about miscarriage and grief counseling. I wondered if our paper is frivolous in comparison to the others. I think not. Our episodes of cultural starvation and indifference are there and painful, but our comebacks are so quick (nourishment as resistance), and therefore so is the celebration. Written by Agosto while flying home after presenting at the 2014 International Congress of Qualitative Inquiry.
Keywords: dept.cur

Adoptive Parents’ Suspicion and Coping With the Possibility of Child Abduction for International Adoption in China - Marn, Travis M.; Tan, Tony Xing (The Family Journal, 2015)
In this study, we investigated (1) whether adoptive parents suspected their children might have been victims of abduction for adoption in China and (2) for parents who were uncertain if their own children might be victims of child abduction for adoption, how they coped with the possibility. A total of 342 adoptive parents (representing 529 adopted Chinese children) completed an anonymous online survey on their experiences. Of the 342 parents, 154 (45%) described how they coped with the possibility that their children might be the victims of child abduction for adoption. In terms of suspicion, we found that for about 70% of the children, the parents responded Never; for 18.5% of the children, the parents responded Rarely; for 11.7% of the children, the parents responded Sometimes; and for about 1% of the children, the parents responded that they Always suspected that their children might be victims of abduction for adoption. In terms of coping with the possibility that their children might have been victims of child abduction for adoption, thematic analysis on the 154 parents’ descriptions revealed that parents experienced one or more of seven emotional reactions: sadness, frustration/helplessness, complicity/guilt, anger, fear/worry, hypervigilance, resolve, as well as the belief that they were not affected. Finally, we discussed contributing factors to child abduction for adoption and to adoptive parents’ suspicion of such a practice.
Keywords: dept.cur

Creating a Space for Teacher Candidates Committeed to Urban Settings: Action Research Program on the Urban Education Fellows Program - Bower-Phipps, Laura; Marx, H. A. (Teacher Education Yearbook XXIV: Establishing a Sense of Place for All Learners in 21st Century Classrooms and Schools, 2015)
The Association of Teacher Educators (ATE) Yearbook XXIV offers 16 captivating chapters related to establishing a sense of place or belonging for P-12 students, classroom teachers, teacher candidates, and teacher educators. The chapters include theory, research, concepts, principles, practices, and programs that inform and support as well as question and challenge readers from multiple perspectives. Readers gain insights and inspiration that illustrate ways teachers and learners negotiate meaning in environments where everyone experiences social and cultural connections with personal and academic fulfillment. Collectively, the authors identify, describe, analyze, and advance issues associated with creating both an individual and a shared sense of place among the ever-changing populations in contemporary P-12 schools and classrooms. Like human geographers, teacher educators and educational researchers study environments where children grow up and create bonds with their early environments that continue to influence them throughout their lives based on the ways in which meaning is negotiated in that early space. Candidates, teachers, and teacher educators benefit by investigating the presence and power of these landscapes impacting the teaching, learning, and schooling.
Keywords: Education / Administration / General; Education / Educational Policy & Reform / General; Education / Inclusive Education; Education / Learning Styles; Education / Student Life & Student Affairs; dept.cur

Valuing stuff materials culture and artifactual literacies in the classroom - Randall, Regine; Mercurio, Mia Lynn (Journal of Adolescent & Adult Literacy, 2015)
Recent interest in materials culture and artifactual literacies has helped the authors of this article rethink how they teach preservice and inservice teachers and collaborate with K-12 teachers. Each discipline has its own stuff that can help students understand the products and practices of a field beyond what they might be able to glean from text. To that end, every teacher should see their classroom and content area as a "place for my stuff" because objects speak and communicate more messages through form, color, size, and texture than print alone. © 2015 International Literacy Association.
Keywords: 3-Early adolescence; 4-Adolescence; 5-College/university students; Adolescent/young adult literature; Content analyses; Content literacy; Discussion strategies; Information literacy; Informational text; Instructional strategies; Literary elements; Specific subject areas (math; Strategies; Text types; and materials; art; dept.cur; dept.sed; etc.); methods; teaching strategies; text features

Guiding students as they explore, build, and connect online - McVerry, J. Gregory; Belshaw, Doug; O'Byrne, W. Ian (Journal of Adolescent & Adult Literacy, 2015)
Keywords: dept.cur

Improving students' academic learning by helping them access text - Ben-Avie, Michael; Randall, Régine; Dunne, Diane Weaver; Kelly, Chris (Recent Advances in Assistive Technologies to Support Children with Developmental Disorders, 2015)
Conventional methods of addressing the needs of students with print disabilities include text-to-speech services. One major drawback of text-to-speech technologies is that computerized speech simply articulates the same words in a text whereas human voice can convey emotions such as excitement, sadness, fear, or joy. Audiobooks have human narration, but are designed for entertainment and not for teaching word identification, fluency, vocabulary, and comprehension to students. This chapter focuses on the 3-year pilot of CRISKids; all CRIS recordings feature human narration. The pilot demonstrated that students who feel competent in their reading and class work tend to be more engaged in classroom routines, spend more time on task and demonstrate greater comprehension of written materials. When more demonstrate these behaviors and skills, teachers are better able to provide meaningful instruction, since less time is spent on issues of classroom management and redirection. Thus, CRISKids impacts not only the students with print disabilities, but all of the students in the classroom.
Keywords: dept.cur